Learning strategy implementation of jigsaw to upgrade the academic competency of counselor candidate - Permatasari, Devi (COUNS-EDU: The International Journal of Counseling and Education, 2017)
Peculiarly, the building of academic competency on counselor candidate needs to be gained through activity degree and student learning outputting class. Student academic competency in work skill on guidance and counseling course, notably in management and evaluation of guidance and counseling course require for having knowledge on theoretic treasures, context, principle, procedure and tools used in performing guidance and counseling service, also in developing professionalism as counselor on an ongoing basis by practicing guidance and counseling performance procedurally in school. Academic competency that will be gained by student can be categorized in three aspects of academic competency accomplishment, which are cognitive, affective, and psychomotor. The researcher concludes that the lack of those three aspects above caused by the learning process in class which is expository, that giving less attention on learning experience organization. So, the study content tends to be forgotten easily. The using of jigsaw learning is expected to facilitate e-learning experience organization of the student in improving academic competency of counselor candidate. Classroom action research is implemented in three cycles. The result gained in each cycle is increase gradually. Cycle I shows that the development of student academic competency is still on low rank, cycle II shows medium average development of student academic competency, cycle III shows that the average development of student academic competency is on high rank. The implementation this learning strategy can be used to improve the learning process by prioritizing on academic competency through study activity and learning output of the student. As the process improvement, the researcher focuses on student learning, so that the lecturer has the role as facilitator only.